Smart Manufacturing for Smart Cities—Overview, Insights, and Future Directions - Suvarna, Manu; Büth, Lennart; Hejny, Johannes; Mennenga, Mark; Li, Jie; Ng, Yen Ting; Herrmann, Christoph; Wang, Xiaonan (Advanced intelligent systems, 2020)
With ‘smart’ being the order of the day, the shift in the landscape of a typical production‐oriented manufacturing environment to a more data‐oriented, automated and smart manufacturing is imminent. However, what is meant by smart manufacturing? And how can smart manufacturing contribute to a bigger picture by acting as enablers of smart cities? Given the paucity in literature that seeks to make sense in this direction, herein, first, six indices that represent or define a smart city are identified. Then, a holistic perspective of smart manufacturing is presented by collectively dwelling into the concepts of cyber physical production systems (CPPS) and industrial symbiosis—the recent and ongoing developments, applications, and relevant examples. In each subsequent section, the Review addresses how smart manufacturing contributes to smart cities, not just from a technology perspective, but also by satisfying the ergonometric factors and sustainability issues which are equally important indices that make up a smart city. A brief overview of Singapore as a smart nation and smart manufacturing hub is presented toward the end, along with highlights of a real‐world smart manufacturing platform called the Model Factory and its relevant modules. Herein, a holistic perspective on the role and contribution of smart manufacturing toward smart cities is presented by collectively dwelling into the concepts of cyber physical production systems (CPPS) and industrial symbiosis. In general, it is addressed how smart manufacturing contributes to smart cities from the perspectives of state‐of‐the‐art digital technologies, ergonometric factors, and sustainability issues.